Linguocultural features of subcolloquial phraseological units - Otaqulov, Nodirjon (The Lingua Spectrum, 2025)
This article presents a comprehensive linguistic analysis of the linguoculturological features of subcolloquial phraseological units in French and Uzbek. The study identifies the place of subcolloquial phraseologisms within the language system and explores their communicative-functional, social-discursive roles, as well as their stylistic-functional characteristics. The findings contribute to the linguoculturological classification of subcolloquial phraseological units and reveal their reflection in the cultural consciousness of different nations. The relevance of this research is directly linked to the sociolinguistic processes emerging in contemporary society, particularly the widespread use of colloquial and subcolloquial lexical-phraseological units in spoken language and communicative practice. These linguistic elements, which are prevalent in the speech of various social groups, have not yet been sufficiently investigated within the framework of modern linguistics. Determining their linguoculturological properties and the extent of their association with national and cultural codes represents one of the pressing issues in contemporary linguistic studies, analyzed based on theoretical frameworks and empirical observations.